Role of teacher in handling the bullying behavior in students of elementary school - Muchlish, Imam Jauhar; Indriani, Faras; Mardefi, Novmiasti Sela; Hernadi, Tri (Universitas Ahmad Dahlan, 2023)
This research aims to describe the role of teachers in dealing with bullying behavior in students in grades I to VI at SD Negeri Balirejo, one of public elementary schools in Yogyakarta, Indonesia. This research uses a qualitative approach. Subjects in this research include teachers and students at school. The data collected in this research are processed through data reduction, data presentation, and conclusion. Based on the research results, the role of class teachers in dealing with bullying, namely (1) as a mediator and facilitator, by cultivating positive relationships, encouraging good social behavior, and seeking learning resources; (2) as a guide by providing explanations and actions when bullying occurs; (3) as an advisor by providing advice; and (4) giving sanctions, put up posters of positive habits.